2014
DOI: 10.1002/phar.1398
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic Testing for Neuropsychiatric Drugs: Current Status of Drug Labeling, Guidelines for Using Genetic Information, and Test Options

Abstract: Advancements in pharmacogenomics have introduced an increasing number of opportunities to bring personalized medicine into clinical practice. Understanding how and when to use this technology to help guide pharmacotherapy used to treat neuropsychiatric conditions remains a challenge for many clinicians. Currently, guidelines exist to assist clinicians in the use of genetic information for drug selection and/or dosing for the tricyclic antidepressants, carbamazepine, and phenytoin. Additional language in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 48 publications
1
51
0
Order By: Relevance
“…Genetic factors and clinical characteristics contribute to the failure of a favourable treatment outcome [4,5]. A large number of genes are likely to influence the toxicity and response of an individual medication of antidepressant response [1][2][3][4][5][6][7][8][9][10][11][12][13][14]15]. A recent study focused on determination of the effect of the CYP2D6 genotype on the length of hospitalization stay for patients treated for major depressive disorder and found that the hospital stay was significantly longer in deficient CYP2D6 metabolizers compared with functional or supra-functional metabolizers [16].…”
Section: Current Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic factors and clinical characteristics contribute to the failure of a favourable treatment outcome [4,5]. A large number of genes are likely to influence the toxicity and response of an individual medication of antidepressant response [1][2][3][4][5][6][7][8][9][10][11][12][13][14]15]. A recent study focused on determination of the effect of the CYP2D6 genotype on the length of hospitalization stay for patients treated for major depressive disorder and found that the hospital stay was significantly longer in deficient CYP2D6 metabolizers compared with functional or supra-functional metabolizers [16].…”
Section: Current Findingsmentioning
confidence: 99%
“…Importantly, Federal agencies, including the Department of Health and Human Services and the US Food and Drug Administration (FDA) are incorporating pharmacogenomics dosing guidance into the labelling, development, and approval of drugs in a manner that supports gene-based care in more than 110 medications. Of the 32 neuropsychiatric drugs listed, 27 (84%) have CYP2D6 metabolizer status, 3 (9%) identify CYP2C19 metabolizer status and 3 (9%) pertain to other important genetic markers (e.g., HLA-B) [12]. Dosing information is also available for CYP2D6, CYP19, and HLA-B poor metabolizers (PM) [17,18], for example, CYP2D6 is responsible for oxidative metabolism of up to 25% of medications [19], including a large subset of antidepressants and antipsychotic medications.…”
Section: Current Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consensus guidelines will be necessary to inform clinicians on which biomarkers are useful and how they can be implemented in daily clinical practice (cf. Drozda et al 2014). At the patient level, education and teaching regarding advances and limitations in the field are germane to a realistic understanding of the benefits of personalized medicine.…”
mentioning
confidence: 99%
“…Because of inter-ethnic heterogeneity, the dosage established in a landmark trial and clinical pharmacogenetics applications for a certain population may not be generalizable to other ethnic populations and a follow-up study is often needed to find the maximum tolerated dose for different populations. This problem even exists in various ethnic sub-populations [24].…”
Section: Cyp2d6mentioning
confidence: 99%